OPTIMIZATION OF METHODS FOR THE DIAGNOSIS AND TREATMENT OF ORAL MUCOSAL DISEASES (The New Uzbekistan Journal of Medicine, 2025)
Diseases of the oral mucosa represent one of the most common pathologies in dental practice. The diagnosis of such conditions requires a comprehensive approach, including clinical, laboratory, and instrumental examinations. The aim of this study is to develop and implement optimized methods for the diagnosis and treatment of oral mucosal diseases using modern technologies and a personalized approach. Based on the analysis of 120 clinical cases, the effectiveness of various diagnostic methods (cytology, PCR analysis, dermatoscopy) and treatment regimens (anti-inflammatory, antiseptic, and immunostimulating agents) was evaluated. The results showed that a comprehensive approach increases diagnostic accuracy and improves clinical outcomes in patients.